2016
DOI: 10.1158/2159-8290.cd-16-0267
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Alteration and Dysregulation of the Hippo Pathway in Mucinous Tubular and Spindle Cell Carcinoma of the Kidney

Abstract: Mucinous tubular and spindle cell carcinoma (MTSCC) is a relatively rare subtype of renal cell carcinoma with distinctive morphologic and cytogenetic features. Here we carry out whole exome and transcriptome sequencing of a multi-institutional cohort of MTSCC (n=22). We demonstrate the presence of either biallelic loss of Hippo pathway tumor suppressor genes (TSGs) and/or evidence of alteration of Hippo pathway genes in 85% of samples. PTPN14 (31%) and NF2 (22%) were the most commonly implicated Hippo pathway … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…Activation of Lats1/2 by PtpnN14 may also have the additional effect of stimulating p53 activity by binding Mdm2, driving a positive feedback loop for p53 activity (Aylon et al, 2006; Matallanas et al, 2011). Our data highlighting the requirement of Ptpn14 in tumor suppression has been bolstered by recent human cancer genome studies in which PTPN14 was shown to be mutated in both kidney cancer and basal cell carcinoma, leading to Yap nuclear localization (Bonilla et al, 2016; Mehra et al, 2016). These observations are in keeping with studies in immortalized mammary cell lines, in which Ptpn14 knockdown enhances colony growth (Liu et al, 2013; Michaloglou et al, 2013; Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Activation of Lats1/2 by PtpnN14 may also have the additional effect of stimulating p53 activity by binding Mdm2, driving a positive feedback loop for p53 activity (Aylon et al, 2006; Matallanas et al, 2011). Our data highlighting the requirement of Ptpn14 in tumor suppression has been bolstered by recent human cancer genome studies in which PTPN14 was shown to be mutated in both kidney cancer and basal cell carcinoma, leading to Yap nuclear localization (Bonilla et al, 2016; Mehra et al, 2016). These observations are in keeping with studies in immortalized mammary cell lines, in which Ptpn14 knockdown enhances colony growth (Liu et al, 2013; Michaloglou et al, 2013; Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Our previous finding that PTPN14 is targeted for degradation by high-risk HPV E7 but not by low-risk HPV E7 suggested that PTPN14 loss might be related to the biology of the high-risk HPV (47). PTPN14 is a candidate tumor suppressor based on the observation that it is mutated in some cancers (54,57,(78)(79)(80)(81). The targeted degradation of PTPN14 by high-risk HPV E7 requires the E3 ubiquitin ligase UBR4 and the interaction of UBR4 with papillomavirus E7 is required for E7 to transform cells (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous finding that PTPN14 is targeted for degradation by high-risk HPV E7 but not by low-risk HPV E7 suggested that PTPN14 loss might be related to the biology of the high-risk HPV (47). PTPN14 is a candidate tumor suppressor based on the observation that it is mutated in some cancers (54, 57, 7881). The targeted degradation of PTPN14 by high-risk HPV E7 requires the E3 ubiquitin ligase UBR4 and the interaction of UBR4 with papillomavirus E7 is required for E7 to transform cells (45, 46).…”
Section: Discussionmentioning
confidence: 99%